Peningkatan Kemampuan Pemecahan Masalah Matematis Melalui Pembelajaran Berbasis Masalah Pada Siswa Kelas X SMK Ar-Rahman Medan - Sari, Nilam; Ompusunggu, Vera Dewi Kartini; Daliani, Muhammad (JURNAL PEMBELAJARAN DAN MATEMATIKA SIGMA (JPMS), 2020)
This study aims to determine: Is increasing the ability of mathematical problem solving students who get problem based learning better than students who get conventional learning. This research is a semi-experimental study with the study population as all students of all grade X students of SMK AR-Rahman Medan. The sample selection is done randomly and 2 classes are chosen. The instrument used is a test of problem solving skills with the material system of linear equations. Data in this study were analyzed using parametric analysis. Statistical analysis of data was performed by t test analysis. The results showed that: (1) Increased mathematical problem solving abilities of students who obtained problem-based learning were higher than students who obtained conventional learning; (2) There is a significant difference between improving students' mathematical problem solving abilities that obtain problem-based learning and students who obtain conventional learning; (3) Among the four aspects of problem solving, the highest average increase in the aspect of "making a mathematical model" of 0.635 with moderate criteria. Based on the results of this study, researchers suggest that problem-based learning in students can be used as an alternative for teachers to improve students' problem solving abilities, especially in the Linear Equation System material